Thinking and Working Politically: What does it mean, Why is it importa nt and How do you do it? - Leftwich, Adrian (DLP, 2011)
This paper suggests that working politically in a developmental contex t means directing attention and support to the agents of reform and de velopment (leaders and organisations). This allows investment in the l ocal processes that will resolve problems – such as problems of collec tive action – through the work of alliances and coalitions. Hence, it will drive the formation and consolidation of the locally appropriate, feasible and legitimate institutions that are most likely to advance development outcomes. The Developmental Leadership Program defines pol itics as the pervasive, unavoidable and necessary activities of confli ct, negotiation and compromise involved in group decision-making about how resources are to be used, produced and distributed. Thinking poli tically means understanding that both political and technical dimensio ns are central to developmental outcomes. It also means: Understanding that ‘agency’ matters. That is, that people have the potential to cha nge things, but always withhin the context of given institutional arra ngements, which contain both constraints and opportunities. Leaders, o rganisations and followers think, strategise and attempt to resolve pr oblems in different ways in the same contexts. Understanding leadershi p as a political process that mobilises people and resources in suppor t of a goal: leaders seldom work on their own. Realising that overcomi ng collective action problems is a major challenge of development. Col lective action problems occur when people with diverse (often competin g) interests struggle to agree on an organisational arrangement from w hich they would all benefit. Understanding that coalitions (formal or informal) are a crucial political mechanism for the resolution of coll ective action problems. Paying attention to the detailed inner politic s of regimes, sectors or issues (‘micro-politics’). This includes unde rstanding who the players are, where they come from, their organisatio nal affiliations, ideologies and interests and the political dynamics involved. (Many political analysis tools are inadequate for this level of detail.) Recognising that processes are as important as projects i n development, and vary from context to context. Working politically i n development means supporting, brokering, facilitating and aiding the emergence and practices of (public or private) developmental or refor m leaderships, organisations, networks and coalitions at any level, an d across all sectors. It means helping them to respond to, and work wi th, initiatives and requests from local individuals and groups. Workin g politically can also involve: Investing in the effectiveness of deve lopmental coalitions by enhancing the political capacity of organisati ons in negotiation, advocacy, communication and the generation of cons tructive policy options. Rethinking higher educational support program mes so that they supplement a skills focus with strategies that help t o build networks, and encourage the understanding of collective action problems and of the importance of providing public goods. Acquiring a deep and detailed knowledge of, and long-term exposure to, the countr y or issue concerned. Respectful and sensitive understanding of local political dynamics and cultural norms. Employing more social scientist s and a well-trained, politically savvy workforce, both local and inte rnational, with the capacity to ‘read’ the politics. In particular, co alitions can help drive the endogenous politics of developmental refor ms by: 1) achieving a specific policy goal; 2) opening up debate on a previously taboo issue; 3) deepening and strengthening the coalition’s internal organisation and relationships for future purposes; and 4) i ncreasing the capacity of constituent organisations. It is also import ant to understand that: Developmental leaderships and coalitions often emerge in response to a critical juncture – a threat, challenge or da nger – or a new opportunity. What matters is whether leaders have the knowledge, education, vision, prior experience and networks to seize s uch opportunities. The character and conditionality of funding by dono rs or supporters can make or break a coalition. Are tight conditions a pplied? Are funding arrangements transparent?